2021
DOI: 10.1159/000520310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineralocorticoid Receptor Antagonists on the Prognosis of Patients with Ventricular Tachyarrhythmias

Abstract: <b><i>Introduction:</i></b> The study sought to assess the effect of treatment with mineralocorticoid receptor antagonists (MRAs) on long-term prognosis of patients with systolic heart failure (HF) surviving index episodes of ventricular tachyarrhythmias. <b><i>Methods:</i></b> A large retrospective registry was used including consecutive HF patients with left ventricular ejection fraction &#x3c;45% and index episodes of ventricular tachyarrhythmias from 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Regarding the therapeutic role of MRA treatment in patients with VA, it has been explored in a retrospective registry recently published. In HF survivors after ventricular tachyarrhythmia (LVEF ≤45%, mean age 66 years, 20% women), treatment with MRA was not associated with improved all-cause mortality at 3 years follow-up [55]. However, only 20% of patients with HF who survived ventricular tachyarrhythmia were discharged with MRA.…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%
“…Regarding the therapeutic role of MRA treatment in patients with VA, it has been explored in a retrospective registry recently published. In HF survivors after ventricular tachyarrhythmia (LVEF ≤45%, mean age 66 years, 20% women), treatment with MRA was not associated with improved all-cause mortality at 3 years follow-up [55]. However, only 20% of patients with HF who survived ventricular tachyarrhythmia were discharged with MRA.…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%
“…[12][13][14] Some studies have shown that the change of urea nitrogen in the early stage of patients with AP is related to the prognosis, and the results of this study are inconsistent with them, which may be due to the differences in the disease characteristics of the included patients and the limitation of sample size. [15][16][17][18] Balthazar CT grading is a grading method to evaluate the lesions of pancreatic parenchyma and surrounding tissues according to pancreatic morphology, inflammation and other conditions. [19,20] Studies have shown that the larger the volume of necrosis in the pancreas and peripancreatic area, the higher the density of necrosis, the slower the absorption and dissipation, the more serious the erosion effect on peripancreatic tissue, and the larger the CT attenuation value.…”
Section: Discussionmentioning
confidence: 99%